PEMERIKSAAN FARMAKOGNOSTIK DAN SKRINING KOMPONEN KIMIA HERBA SURUHAN (Peperomia pellucida L.(Kunth).) ASAL KOTA MAKASSAR - Asni Amin; Martati Martati (As-Syifaa Jurnal Farmasi, 2009)
Peperomia pellucida  is  tradisional medicine used for treatment of hay fever, hipotensi, diuretic, and stomatichum in  Sulawesi Selatan, This research aimed to get data of morphology, anatomy and also data of physis and chemical from Suruhan for development of its for drug.  Sample extraction with methanoll 95%, physis data included content water soluble extractive 8,68%, dilute etanol soluble extractive 15,04 %, total ash  4 %, water insoluble ash  2,75%, acid insoluble ash  4,24%, identification by using chemical analysis to the powder of herb resulted alkaloid, steroid, tannin, lignin, pati, aleuron, and profil of TLC is steroid. Identification of morphology showed that Suruhan was Herb, wet bark, leaf simple, cordatus, strongly green, flowers are very small in dense spikes. Assay  anatomy to bark showed closed collateral vessel bundle, calsium oxalate crystal, transverse section of leaves indicated that epidermis with stomata type is anisositik, hypodermis, palisade, spons, vesicle bundle, and calsium oxalate crystal.Key Words : Identification, Piperomia pellucid